Training strategy development of explosive strength in volleyball - Cretu, M.; Vladu, L. (Journal of Physical Education and Sport, 2010)
The muscular training is one of the most important factors and in some cases the most important admixture of sport training, with a view to reaching high performances, influencing the way the preparation is undergone. This training must be completed on a uniformly and balanced basis for each of the motric aptitudes required by the performance sport. The purpose of this paper is that of improving the muscular preparation by introducing alternate contracts schemes inside the training of the volley players (16-18 years).